PRELIMINARY RESULTS OF THE REACTION OF CYCLOTRIMERIZATION OF PHENYLACETYLENE [2+2+2] CATALYZED BY [(Cp*)Co(Indene)] COMPLEX - Cesar Morales-Verdejo; María Belén Camarada; Verónica Morales; Álvaro Cañete; Iván Martínez; Juan Manuel Manriquez; Ivonne Chávez (Journal of the Chilean Chemical Society, 2018)
This work describes the catalytic study of [(Cp*)Co(Ind)] (with Cp*= pentamethylcyclopentadienyl, Ind= Indenyl, (C9H7)) complex in cyclotrimerization of phenylacetylene. From the cylcotrimerization reaction was possible to obtain products such as substituted pyridines 2-methyl-3,5-diphenylpyridine (3), 2-methyl- 4,6-diphenylpyridine (4) and the compound 1,2,4-triphenylbenzene (5) using acetonitrile as solvent. On the other hand, using toluene as solvent under the same working conditions, the product of reaction was 1,3,5-triphenylbenzene (1). Furthermore, by varying the working conditions, the reaction is 90% selective towards the formation of pyridines. In addition, has been appreciated the formation of another product 1,4-diphenilbuta-1,3-diyne (2), which was isolated and characterized by means NMR and GC-Mass spectrometry.